Melitopalynological and antimicrobial properties of honeys from Elazi? (E Turkey) - Gür, N.; Di?rak, M.; Çobano?lu, D.; Dilsiz, N. (Akademiai Kiado Rt., 2001)
In this study, the pollen analyses and antimicrobial effect were conducted in honey samples, which were collected from seven localities where apiculture has intensively been practiced. Upon pollen analyses of 16 different plants have been determined. The plants contributing nectar to honey samples in Elazi? were found as follows; Fabaceae: Astragalus, Trifolium, Vicia, Onobrychis; Asteraceae: Centaurea triumfettii, Carduus, Xeranthemum, Helianthus annum; Lamiaceae: Salvia, Mentha; Rosaceae: Rubus, Prunus; Vitaceae: Vitis; Apiaceae: Daucus; Zygophyllaceae: Peganum harmala; Ranunculaceae: Ranunculus. The honey samples have inhibited the growth of bacteria used in our work at varying degrees. None of the samples had any antifungal effect against Candida albicans FMC-17 and Saccharomyces cerevisiae UAG-102. © 2001 Akadémiai Kiadó.
Keywords: Antimicrobial properties; Honey; Pollen grains